LEARNING STYLES IN DIDACTIC PLANNING OF HIGHER EDUCATION - Morales, Beatriz Eugenia Cárdenas; Velasco, Ma. del Carmen Cid; Jerónimo, Julia Matilde Hernández; Cruz, María Isabel Azcona (Seven Editora, 2025)
Objective: To develop a methodological proposal to identify the characteristics of the students in a group (personality, academic level, context, cognitive structure and learning styles), to guide didactic planning towards comprehensive training, meaningful and personalized learning.Theoretical Framework: Students with heterogeneous characteristics in their biography and academic history converge in the classroom.  Its identification by means of various diagnostic models (Briggs-Myer; Honey-Mumford; Kolb; VARK; 4MAT-System) allows for the adaptation of didactic planning improving students' academic results.Method: A qualitative, descriptive, literature review study was carried out, analyzing didactic planning and several models of learning styles, to develop a methodological proposal that identifies the characteristics of students in a school group (personality, academic level, context, cognitive structure, learning styles).Results and Discussion: The characteristics and learning styles identified by the models reviewed are  personality (Briggs-Myer), attitude and behavior (Honey-Mumford; Honey-Alonso), experiential learning (Kolb), preferential sensory modality for perceiving and processing information (VARK, Fleming-Mills model), laterality and specificity of the cerebral hemispheres (Bernice McCarthy's 4MAT-System), interaction between students and teachers (Grasha-Riechmann). It included also an initial diagnostic examination, individual and group interviews and team building.Research implications: Didactic planning oriented towards the characteristics and learning styles of students is an innovative strategy to achieve meaningful and personalized learning.Originality/Value: The relevance of the study is to emphasize the need to identify the differences between the students of a group, in order to generate changes both in didactic planning and at the institutional level, benefiting the community.DOI: https://doi.org/10.56238/sevened2025.036-151